Website Based Sales Information System With The Concept Of Mvc (Model View Controller): Website Based Sales Information System With The Concept Of Mvc (Model View Controller) - Zulfahmi Syahputra (Institute of Computer Science (IOCS), 2020)
Website is a form of mass media that is published through the internet that can be accessed anywhere and anytime. At present many trading companies are selling a product using a website, such as PT. Indofood Medan is expected to make it easier for both the sales and reporting sides. The quality of a Website is very necessary for the attractors and attractors of users to carry out the buying and selling process on the website, by using the Model View Controller (MVC) the appearance and usefulness of a website will look more attractive